ANALYSIS OF THE ELECTRE METHOD IN DECISION SUPPORT SYSTEMS FOR DETERMINING AREAS OF EXPERTISE FOR INFORMATICS MANAGEMENT STUDY PROGRAM STUDENTS - Sugih Hati Musti; Deci Irmayani; Gomal Juni Yanris (Sean Institute, 2021)
Confusion of students in concentrating on the field of science in the Informatics Study Program Univ. Labuhan Batu becomes a problem for students in writing a thesis. Informatics Engineering Study Program Univ. Labuhan Batu has a group of experts that is intended to direct students' thesis titles according to their fields. Elimination Choice and Translating Reality (ELECTRE) is the method used in this study. The ELECTRE method is a method that can produce decisions by comparing alternatives in pairs on the same criteria. The results obtained from this application are to provide a recommendation value in the form of a ranking based on the relationship between the alternatives and the criteria entered. The purpose of this research is to produce recommendations for areas of expertise for students of the Informatics Study Program Univ. Stone Labyrinth. System testing is done in two ways, namely black box testing and accuracy testing. Black box testing is done to test the functionality of the application based on the input entered. While the accuracy test is to see how much accuracy or suitability of the skill group students has with the results of the system recommendations.